A Brief Note on a Life That Left a Mark - Femenías, María Luisa (2025)
Those of us who have studied the work of Simone de Beauvoir cannot ignore at least two names: Celia Amorós—the Teacher—and Teresa López Pardina—the first thesis in Spanish to pay homage to the French thinker, unequivocally designating her as a Philosopher. Today, we owe Teresa our modest tribute.